ONLINE MARKETING STRATEGY ON SMALL AND MEDIUM MICRO ENTERPRISES (MSMEs) KERUPUK MELARAT IN SINARMUKTI VILLAGE - Yuniarsih Yuniarsih; Rizky Ariansyah Siregar; Nurrohman Nurrohman; Anton Nasrullah; Mutia Anjani; Iim Soimin; Rani Puspa (Yayasan Education and Social Center, 2021)
Business actors must have the ability to manage online marketing. Social media as a marketing tool aims to expand the reach of consumers in various cities to increase sales of Small and Medium Micro Enterprises (MSMEs)